PENGARUH PENGGUNAAN LKS BERMUATAN KECERDASAN KOMPREHENSIF MENGGUNAKAN MODEL PBL TERHADAP KOMPETENSI SISWA SMAN 3 PADANG - Elhidayah Dwi Fitri; Akmam Akmam; Gusnedi Gusnedi (PILLAR OF PHYSICS EDUCATION, 2016)
Physics learning outcomes of Senior High School in Padang is not optimum. It caused by student worksheet which use student was not support to reach optimum learning outcomes. For this reason student worksheet that support optimally learning outcomes must be develop. A research was doing to investigate influence the student worksheet which be equipped by comprehensive intelligence in Problem Based Learning to physics learning outcomes for grade X in Senior High School 3 Padang must be done. Population of Quasi Experiment Research with randomized control group only design was student for grade X MIA in Senior High School 3 Padang registered on 2015/2016. Technique sampling this research was purposive sampling. Instrument research was objective test sheet for cognitive, observation sheet for spiritual and social attitude and performance rubric for psychomotor. That result of research showed that the mean score of the experiment class is high than control class. Analysis of data that worksheet which be equipped by comprehensive intelligence in problem based learning was influence significantly to physics learning outcomes for grade X in Senior High School 3 Padang